Optogenetic activation of intracellular adenosine A2A receptor signaling in the amygdala as a model of stress in rodents - Carreira, Catarina Bernardino (2021)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia